Pengaruh Adisi Nano-TiO2 pada Bahan Bakar Diesel Pertamina Dex pada Emisi Gas Buang - Dharmawan, Aditya; Pasha, Pangeran Rafli; Putra, Restu Ramadhani Pratama (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
The increase in the number of diesel vehicles in Indonesia leads to increased demand for diesel fuel energy, so the use of fuel must be managed as effectively and efficiently as possible. In this research, the addition of TiO2 nanoparticle additives to Pertamina Dex was carried out, using ultrasonic bath method. Each batch of synthesis was carried out in a capacity of 200 mL for 20 minutes, with a loading variation of Nano-TiO2 in Pertamina Dex from 0 mg/L to 200 mg/L. Then they were tested for physical properties such as density, viscosity, flash point and calorific value. They also tested for emission test. It was found that physical properties such as density, viscosity, flash point and calorific value of Pertamina Dex-Nano TiO2 did not change significantly. As of emission test, hydrocarbon emission test result showed 80% decrease, NOx emission test result showed 51% decrease, CO emission test result showed 47% decrease, CO2 emission test result showed 29% increase. Decrease of NOx achieved by lowering peak flame temperature after Nano-TiO2 was added. Decrease of hydrocarbon, decrease of CO and increase of CO2 emission achieved by higher rate of perfect combustion, from O2 supplied by Nano-TiO2.